1989
DOI: 10.1159/000185327
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes in the Subtotally Nephrectomized Rat Fed Differing Dietary Proteins

Abstract: Changes in body composition are found in chronic uraemia, but it is unclear if this results from poor nutrient intake or is a consequence of impaired renal function. To investigate this question, 31 female Wistar rats were allocated to undergo subtotal nephrectomy or sham operation and were fed diets of either 24% casein or 24% soya protein. Three months later measurements of inulin clearance were undertaken in the conscious animal and the carcass subsequently analyzed for body water and body fat. Subtotally n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Rats with uninephrectomy developed chronic proteinuria in association with massive deposits of lipids, which were shown to consist mainly of free and esterified cholesterol, 23 as have prior studies in subtotally nephrectomized animals demonstrated a significant correlation between glomerular filtration rate and body fat content. 24 Consistent with the present study, the renal impairments and lipid deposition were generally prevented by ACEI treatments in Nagase analbuminemic rats, after 5/6 nephrectomy, which usually exhibit severe glomerulosclerosis, persistent hypercholesterolemia, and massive lipid deposition. 25 Additionally, clinical studies using computed tomography have previously demonstrated a significant decrease in body fat area and subcutaneous adipose tissue in parallel to an increase in visceral fat mass associated with disturbance of the serum lipid profile in non-diabetic hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…Rats with uninephrectomy developed chronic proteinuria in association with massive deposits of lipids, which were shown to consist mainly of free and esterified cholesterol, 23 as have prior studies in subtotally nephrectomized animals demonstrated a significant correlation between glomerular filtration rate and body fat content. 24 Consistent with the present study, the renal impairments and lipid deposition were generally prevented by ACEI treatments in Nagase analbuminemic rats, after 5/6 nephrectomy, which usually exhibit severe glomerulosclerosis, persistent hypercholesterolemia, and massive lipid deposition. 25 Additionally, clinical studies using computed tomography have previously demonstrated a significant decrease in body fat area and subcutaneous adipose tissue in parallel to an increase in visceral fat mass associated with disturbance of the serum lipid profile in non-diabetic hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…23 In rats, it seems to be well-established the ability of soy protein to reduce proteinuria and, consequently, to lower the progression of renal disease. 4,24 Tovar et al 3 observed, in male Wistar rats that were receiving a soy protein diet (20%), a considerable recovery of creatinine clearance and a significant decrease in proteinuria compared with rats that were fed with casein (20%). Some investigators 14,24,25 have shown lower renal damage and proteinuria in rats fed with soy protein than those with casein.…”
Section: Discussionmentioning
confidence: 99%